Clinical Importance of Non-Donor-Specific HLA Antibodies and Possible Impact on Graft Histology in Kidney Transplant Recipients – 12 Months Protocol Biopsy Study. (July 2018) - Severova, Galina; Nikolov, Igor; Sikole, Aleksandar; Cakalaroski, Koco; Popov, Zivko; Ivanovski, Ninoslav
Abstract : Background: The association of Donor-Specific HLA Antibodies (DSA) with antibody-mediated rejection (AMR) is already very well known and confirmed by many studies. However the role of circulating Non-DSA HLA antibodies (Non-DSA) is still controversial. The aim of our study is to investigate the clinical importance of Non-DSA associated with 12 month graft histology in regular patients follow up. Methods: Sixty predominantly living donor kidney transplant recipients were involved in a 12 months protocol biopsy prospective study. De Novo DSA and Non-DSA were followed before, up to 3 and 12 months after the surgery by use of Luminex SAB procedure and only those with MIF >800 were considered positive. After 12 months a routine protocol biopsy was performed in all recipients. The presence of AMR was confirmed according to the BANFF 2013 recommendation. In the same time, a semiquantitative Complement 3 (C3) Immunofluorscence (IF) on frozen section was performed in all recipients. Results: In 28 pts DSA and Non-DSA were detected, 4 in DSA and 24 in Non-DSA group. Four pts from DSA group revealed overt deterioration of kidney function and all pts were under the appropriate anti rejection treatment including plasmapheresis, IvIG and Rituximab. The graft histology confirmed predominantly glomerular lesions with a maximum C3 positivity. Twelve pts in Non-DSA group reached the histological criteria for AMR according to the BANFF 2013 with significantly impaired graft function compared with other pts in Non-DSA group (GFR 141.47+22.3 vs. 111.31+ 26.6, respectively. The usual rejection phenotypes were: microcirculation inflammation, glomerular lesions, interstitial inflammation and C3 IF positivity. For the time being, all Non DSA pts are carefully clinically followed. Other 11 pts with non DSA did not show any significant histological lesions and any C3 positivity. The renal function remains normal in all other pts. Conclusion: Data from our study confirm the importance of both, DSA and Non-DSA in the follow up of kidney transplant recipients. The difference between the active and indolent DSA and Non-DSA is determined only by graft histology. Further careful clinical follow up of the recipients with impaired graft histology and detected Non-DSA is necessary regarding decision of the possible therapeutic interventions.